She must and shall go free : Paul's Isaianic Gospel in Galatians - Harmon, Matthew S. (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2010)
Although the significance of the Old Testament for Paul's argument in Galatians is well-established, the significance of Isaiah has not been fully appreciated. Using an intertextual approach, Harmon argues that Isaiah 49-54 in particular has shaped Paul's argument and theology in Galatians. The result is fresh light shed on Paul's self-understanding as an apostle to the Gentiles, the content of his gospel message, his reading of the Abraham story and the larger structure of Galatians.